Lipids and Cardiovascular Organ Damage in Type 2 Diabetes Mellitus - Kozakova, Michaela; Palombo, Carlo (Cardiology and Cardiovascular Medicine, 2020)
One of the mechanisms underlying increased cardiovascular (CV) risk in patients with type 2 diabetes mellitus is atherogenic dyslipidemia, that is characterized by elevated triglycerides and free fatty acids (FFAs) levels, low levels of high-density lipoprotein cholesterol (HDL) and an excess of small dense low-density lipoprotein particles (sdLDLs). Each component of atherogenic dyslipidemia is associated with CV events and triggers alterations at different levels of CV system through different pathways. FFAs and sdLDLs induce endothelial dysfunction, intima-media thickening, plaque formation and arterial stiffening through increase in oxidative stress and inflammation and promoting lipid accumulation and smooth muscle cells (SMCs) proliferation in vascular wall. In contrast, HDL exerts protective effect on arterial wall by increasing nitric oxide availability, by reverse cholesterol transport and by suppression of SMCs proliferation and migration. FFAs overload results in a switch in myocardial substrate utilization, causing changes in myocardial energy metabolism and an increase in baseline oxygen consumption. Accumulation of toxic lipid intermediates in myocardium provokes damage of cellular membrane integrity, organelle dysfunction and apoptosis with consequent decrease in myocardial performance. The structural and functional changes in myocardium can be reversed by therapy with reconstructed HDL. Therefore, the impact of atherogenic dyslipidemia on CV system is not limited on accelerated atherosclerosis, but causes different organ damages that must be considered in their complexity.